powder

By preparing ternary powders of ZnO, Al2O3 and SiO2, controlling their phase diagrams and X-ray diffraction pattern characteristics, the powder problem that is difficult to provide negative thermal expansion coefficients in the prior art is solved, and efficient thermal expansion coefficient management is achieved for electronic components.

JP7657306B2Active Publication Date: 2025-04-04DENKA CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023543717
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-08-23
Filing Date
2022-06-22
Publication Date
2025-04-04
Estimated Expiration
2042-06-22

AI Technical Summary

Technical Problem

The prior art is difficult to provide powders with a negative thermal expansion coefficient, especially in the miniaturization process of electronic components, such powders are required to reduce thermal stress.

Method used

By preparing ternary powders of ZnO, Al2O3 and SiO2, the phase diagram and X-ray diffraction pattern characteristics are controlled to ensure that the content of β-quartz solid solution in the powder reaches more than 50%, and the total content of Li, Na and K is controlled below 500 ppm to achieve a negative thermal expansion coefficient.

Benefits of technology

It is achieved to provide powders with a negative thermal expansion coefficient, suitable for reducing thermal stress in electronic components and improving material stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007657306000005
    Figure 0007657306000005
  • Figure 0007657306000006
    Figure 0007657306000006
  • Figure 0007657306000007
    Figure 0007657306000007
Patent Text Reader

Abstract

One embodiment of the present invention provides a powder. The powder includes ZnO, Al2O3, and SiO2 as components. In a ternary phase diagram of the ZnO, the Al2O3, and the SiO2, the powder has a composition included in a rectangular area having as the four corners thereof (ZnO (mol%), Al2O3 (mol%), SiO2 (mol%)) = ZnO (mol%), Al2O3 (mol%), SiO2 (mol%)) = (24, 13, 63), (19, 18, 63), (37, 12, 51), (32, 17, 51). The ratio (S001 / S101) of the area S001 of a peak appearing in the range of 15º ≤ 2θ ≤ 17º and the area S101 of a peak appearing in the range of 24º ≤ 2θ ≤ 27º in an X-ray diffraction pattern is 0.001-0.07.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a powder. [Background technology]

[0002] In general, powdered fillers are used to improve the properties or functions of substrates such as glass and resin materials. For example, amorphous silica has a particle size of 0.5×10 -6 Since amorphous silica has a small thermal expansion coefficient of about 100 / °C and is relatively easy to obtain, it is used as a filler to control the thermal expansion coefficient of the substrate. However, when it is added to a substrate to be used for bonding, sealing, encapsulation, etc., attention is being paid to a filler with an even smaller thermal expansion coefficient than amorphous silica in order to match the thermal expansion coefficient of the filler with that of the substrate and to suppress the occurrence of thermal stress.

[0003] Many materials, such as zirconium phosphate, zirconium tungstate, and manganese nitride, are known to have a smaller thermal expansion coefficient than amorphous silica. However, these materials have a large specific gravity, and the resin materials, etc., that are mixed with them also become heavy, so they are not commonly used in electronic components, etc. Therefore, there has been active development of lightweight materials with a small thermal expansion coefficient.

[0004] For example, Patent Document 1 discloses that a powder containing the three components ZnO, Al2O3, and SiO2, with the content of each component being 17 to 43 mol % for ZnO, 9 to 20 mol % for Al2O3, and 48 to 63 mol % for SiO2 relative to the total content of the three components, has an excellent effect of reducing the thermal expansion coefficient of the base material when blended into a resin base material. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2019 / 177112 Summary of the Invention [Problem to be solved by the invention]

[0006] Here, in the above-mentioned Patent Document 1, the thermal expansion coefficient of the resin composition to which the powder is added is evaluated, but the thermal expansion coefficient of the powder itself is not evaluated. On the other hand, with the recent trend toward miniaturization of electronic components, there is a demand for powders with a negatively larger thermal expansion coefficient.

[0007] It is an object of the present invention to provide a powder having a more negative coefficient of thermal expansion. [Means for solving the problem]

[0008] According to one aspect of the present invention, a powder is provided. The powder is composed of ZnO, Al2O3, and SiO2. In a ternary phase diagram of ZnO, Al2O3, and SiO2, the powder has a composition included in a quadrangular region having four corners, (ZnO (mol%), Al2O3 (mol%), SiO2 (mol%)) = (ZnO (mol%), Al2O3 (mol%), SiO2 (mol%)) = (24,13,63), (19,18,63), (37,12,51), and (32,17,51), and the area S of the peaks appearing in the range of 15° ≦ 2θ ≦ 17° in the X-ray diffraction pattern is 0.01 to 0.15. 001 and the area S of the peak appearing in the range of 24°≦2θ≦27° 101 Ratio to (S 001 / S 101 ) is greater than or equal to 0.001 and less than or equal to 0.07.

[0009] The present invention may be provided in the following aspects. The powder contains β-quartz solid solution as a crystal phase in an amount of 50 mass % or more based on the total amount of the powder. The powder has a total content of Li, Na and K of 500 mass ppm or less, based on the total amount of the powder. The powder has an average circularity of 0.6 or more. Of course, this is not the case. Effect of the Invention

[0010] According to the present invention, it is possible to provide a powder having a more negative thermal expansion coefficient. [Brief description of the drawings]

[0011] [Figure 1] This is a diagram showing a rectangular region in a ternary phase diagram of ZnO, Al2O3, and SiO2. [Diagram 2] This is an enlarged view of the rectangular region in the ternary phase diagram of ZnO, Al2O3, and SiO2. [Diagram 3] 1 shows X-ray diffraction patterns of powder samples of Examples 1 to 5 and Comparative Example 1. [Figure 4] 1 is a plot of the thermal expansion coefficient in the (112) plane versus the S001 / S101 ratio. [Diagram 5] A plot of the thermal expansion coefficient in the (203) plane versus the S001 / S101 ratio. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, the embodiments of the present invention will be described. The present invention is not limited to the following embodiments, and the respective components shown in the following embodiments can be combined with each other.

[0013] <Powder> The powder according to this embodiment is composed of ZnO, Al2O3, and SiO2. In a ternary phase diagram of ZnO, Al2O3, and SiO2, this powder has a composition included in a quadrangular region having four corners, (ZnO (mol%), Al2O3 (mol%), SiO2 (mol%)) = (24, 13, 63), (19, 18, 63), (37, 12, 51), and (32, 17, 51), and in an X-ray diffraction pattern, the area S of the peak appearing in the range of 15° ≦ 2θ ≦ 17° is 001 and the area S of the peak appearing in the range of 24°≦2θ≦27° 101 Ratio to (S 001 / S 101 ) is greater than or equal to 0.001 and less than or equal to 0.07.

[0014] In the powder having the above-mentioned composition range, the S of the powder 001 / S 101 The ratio and the thermal expansion coefficient are related by a linear function with a negative gradient, S 001 / S 101 However, if the value of the X-ray diffraction pattern is 0.001 or more and 0.07 or less, the thermal expansion coefficient is negatively larger. That is, when the powder has the above-mentioned composition and exhibits the above-mentioned X-ray diffraction pattern, the thermal expansion coefficient is negatively larger.

[0015] The present invention is not limited to a specific theory or mechanism, and the actual mechanism is not clear, but the applicant believes that the reason why the powder has the above-mentioned composition and shows the above-mentioned X-ray diffraction pattern has a larger negative thermal expansion coefficient is as follows. First, in such a range, the content of β-quartz solid solution, which has a larger negative thermal expansion coefficient, becomes large, and the powder as a whole is likely to have a larger negative thermal expansion coefficient. Second, in the X-ray diffraction pattern, the area S of the peak appearing in the range of 15°≦2θ≦17° 001 It is considered that the larger the bias in the probability of existence between interstitial sites of Zn, which is substituted in an interstitial manner in the β-quartz crystal structure, the larger the S 001 The area S of the peak appearing in the range of 24°≦2θ≦27° 101 Ratio divided by S 001 / S 101 is 0.001 or more and 0.07 or less, it means that the bias of the existence probability between the interstitial sites is constant. And such a β-quartz solid solution has a larger negative thermal expansion coefficient.

[0016] In the following, the points (24,13,63), (19,18,63), (37,12,51), and (32,17,51) will be referred to as the “first point,” “second point,” “third point,” and “fourth point,” respectively.

[0017] Figure 1 shows a rectangular region in a ternary phase diagram of ZnO, Al2O3, and SiO2, and Figure 2 shows an enlarged view of the vicinity of the rectangular region in the ternary phase diagram of ZnO, Al2O3, and SiO2.

[0018] The first point is (24,13,63) as described above, but is preferably, for example, (25,13,62), (24,14,62) or (25,14,61).

[0019] The second point is (19,18,63) as described above, but is preferably, for example, (20,17,63), (21,17,62), (22,17,16), (23,17,60) or (24,16,60).

[0020] The third point is (37,12,51) as described above, but it is preferable that the third point is, for example, (36,13,51), (35,13,52), (34,13,53), (33,13,54), (32,13,55), (31,13,56), (30,13,57), or (29,14,57).

[0021] The fourth point is (32,17,51) as described above, but is preferably, for example, (31,17,52), (30,17,53), (29,17,54), (28,17,55), (27,17,56) or (26,17,57).

[0022] The area S of the peak appearing in the range of 15°≦2θ≦17° in the powder X-ray diffraction pattern 001 and the area S of the peak appearing in the range of 24°≦2θ≦27° 101 Ratio to (S 001 / S 101 ) is not particularly limited as long as it is 0.001 or more and 0.07 or less, but is preferably, for example, 0.065 or less, 0.06 or less, 0.055 or less, 0.05 or less, 0.045 or less, 0.04 or less, 0.39 or less, 0.38 or less, 0.37 or less, 0.36 or less, 0.35 or less, 0.34 or less, 0.33 or less, 0.32 or less, 0.31 or less, or 0.3 or less. 001 / S101 may be 0.002 or more, 0.003 or more, 0.004 or more, 0.005 or more, 0.006 or more, 0.007 or more, 0.008 or more, 0.009 or more, or 0.01 or more. 001 / S 101 By being within the required range, the thermal expansion coefficient of the powder can be made negatively large. The area of ​​each peak is obtained by drawing a parabolic background line in the range of 10°≦2θ≦30° using the powder X-ray diffraction pattern comprehensive analysis software Jade 9 manufactured by Materials Data, and then refining and separating the peaks including the background line. Note that the diffraction lines originating from Kα1 and Kα2 overlap in the peaks appearing in the range of 15°≦2θ≦17° and the peaks appearing in the range of 24°≦2θ≦27°, respectively, and this is taken into consideration when performing peak separation. In addition, a pseudo-Voigt function is used as a function of the diffraction peaks in the analysis.

[0023] The powder may contain ionic impurities, which are inevitable impurities, and the content is not particularly limited. The total content of Li, Na, and K as ionic impurities is, for example, 500 mass ppm or less, 450 mass ppm or less, 400 mass ppm or less, 350 mass ppm or less, 300 mass ppm or less, 250 mass ppm or less, 200 mass ppm or less, 150 mass ppm or less, 100 mass ppm or less, 90 mass ppm or less, 80 mass ppm or less, 70 mass ppm or less, 60 mass ppm or less, 50 mass ppm or less, 40 mass ppm or less, 30 mass ppm or less, 20 mass ppm or less, and 10 mass ppm or less, preferably, based on the total amount of the powder. By having the total content of Li, Na, and K be equal to or less than the required amount, the moisture resistance reliability can be improved and the failure of electronic devices can be suppressed. However, the total content of Li, Na, and K may be more than 500 mass ppm based on the total amount of the powder. On the other hand, the Li content may be 0 ppm by mass or more relative to the total amount of the powder (including an embodiment in which the total content of Li, Na and K is 0 ppm by mass, ie, no Li, Na or K is contained).

[0024] The content of Li is not particularly limited, but is preferably 500 mass ppm or less, 450 mass ppm or less, 400 mass ppm or less, 350 mass ppm or less, 300 mass ppm or less, 250 mass ppm or less, 200 mass ppm or less, 150 mass ppm or less, 100 mass ppm or less, 90 mass ppm or less, 80 mass ppm or less, 70 mass ppm or less, 60 mass ppm or less, 50 mass ppm or less, 40 mass ppm or less, 30 mass ppm or less, 20 mass ppm or less, or 10 mass ppm or less, relative to the total amount of the powder. On the other hand, the content of Li may be 0 mass ppm or more relative to the total amount of the powder (including an embodiment in which the content of Li is 0 mass ppm, i.e., no Li is contained).

[0025] The Na content is not particularly limited, but is preferably 500 mass ppm or less, 450 mass ppm or less, 400 mass ppm or less, 350 mass ppm or less, 300 mass ppm or less, 250 mass ppm or less, 200 mass ppm or less, 150 mass ppm or less, 100 mass ppm or less, 90 mass ppm or less, 80 mass ppm or less, 70 mass ppm or less, 60 mass ppm or less, 50 mass ppm or less, 40 mass ppm or less, 30 mass ppm or less, 20 mass ppm or less, or 10 mass ppm or less, relative to the total amount of the powder. On the other hand, the Na content may be 0 mass ppm or more (including an embodiment in which the Na content is 0 mass ppm, i.e., no Na is contained) relative to the total amount of the powder.

[0026] The content of K is not particularly limited, but is preferably 500 mass ppm or less, 450 mass ppm or less, 400 mass ppm or less, 350 mass ppm or less, 300 mass ppm or less, 250 mass ppm or less, 200 mass ppm or less, 150 mass ppm or less, 100 mass ppm or less, 90 mass ppm or less, 80 mass ppm or less, 70 mass ppm or less, 60 mass ppm or less, 50 mass ppm or less, 40 mass ppm or less, 30 mass ppm or less, 20 mass ppm or less, or 10 mass ppm or less, relative to the total amount of the powder. On the other hand, the content of K may be 0 mass ppm or more (including an embodiment in which the content of K is 0 mass ppm, i.e., no K is contained at all) relative to the total amount of the powder.

[0027] The powder may further contain zirconium oxide (ZrO2), titanium oxide (TiO2), etc., in addition to ZnO, Al2O3, and SiO2. The total content of ZnO, Al2O3, and SiO2 is not particularly limited, but is preferably, for example, 90 mol% or more, 91 mol% or more, 92 mol% or more, 93 mol% or more, 94 mol% or more, 95 mol% or more, 96 mol% or more, 97 mol% or more, 98 mol% or more, 99 mol% or more, 99.5 mol% or more, 99.9 mol% or more, 99.95 mol% or more, or 99.99 mol% or more relative to the total amount of the powder. The powder may be composed of only ZnO, Al2O3, SiO2, and unavoidable impurities, or may be composed of only ZnO, Al2O3, and SiO2. By having the total content of ZnO, Al2O3, and SiO2 be greater than or equal to the required amount, the thermal expansion coefficient of the powder can be made larger than the negative amount. On the other hand, the total content of ZnO, Al2O3 and SiO2 may be 100 mol % or less based on the total amount of the powder.

[0028] The powder preferably contains β-quartz solid solution as a crystal phase. The content of this β-quartz solid solution is not particularly limited, but is preferably 50% by mass or more, 55% by mass or more, 57% by mass or more, 60% by mass or more, 62% by mass or more, 65% by mass or more, 67% by mass or more, 70% by mass or more, 71% by mass or more, 72% by mass or more, 73% by mass or more, 74% by mass or more, 75% by mass or more, or 76% by mass or more, based on the total amount of the powder. When the content of the β-quartz solid solution is a required amount or more, the thermal expansion coefficient of the powder can be negatively increased. In addition, when the content of the β-quartz solid solution is a required amount or more, the amount of powder mixed (filled amount) in the base material can be increased, so that the thermal expansion coefficient of the base material can be more easily controlled. On the other hand, the content of the β-quartz solid solution may be 100% by mass or less. The structure of the β-quartz solid solution of the powder can be expressed as xZnO-yAl2O3-zSiO2. The identification of the crystal phase and the measurement of the content can be performed by analyzing the XRD pattern obtained by powder X-ray diffraction using the Rietveld method.

[0029] The powder may further include an amorphous phase in addition to the β-quartz solid solution phase, and may further include other crystalline phases. The powder may include a willemite phase (Zn2SiO4) as the other crystalline phase. The powder may also include a gahnite phase (ZnAl2O4), a mullite phase (Al6SiO2O4), and other crystalline phases. 13 ) and cristobalite phase (SiO2). However, these gahnite phase (ZnAl2O4), mullite phase (Al6SiO2) 13 The total content of the gahnite phase (ZnAl2O4), mullite phase (Al6SiO2) and cristobalite phase (SiO2) is not particularly limited, but is preferably 10 mass% or less, 9 mass% or less, 8 mass% or less, 7 mass% or less, 6 mass% or less, 5 mass% or less, 4 mass% or less, 3 mass% or less, 2 mass% or less, 1 mass% or less, 0.5 mass% or less, 0.2 mass% or less, 0.1 mass% or less, 0.05 mass% or less, 0.02 mass% or less, or 0.01 mass% or less, relative to the total amount of the powder. 13 ) and the cristobalite phase (SiO2) have a positive thermal expansion coefficient, and by keeping the content of these phases below the required amount, the thermal expansion coefficient of the powder can be maintained largely negative. 13 The total content of the crystalline phase (SiO2) and the cristobalite phase (SiO2) may be 0 mass% or more relative to the total amount of the powder (including embodiments in which the content of these crystalline phases is 0 mass%, i.e., the powder does not contain these crystalline phases at all).

[0030] The shape of the powder is not particularly limited, and spherical, cylindrical, prismatic, etc., can be used, with spherical shapes being preferred.

[0031] Whether or not a powder is spherical can be confirmed by calculating the average circularity of the powder. In this specification, the average circularity is calculated as follows. That is, the projected area (S) and projected perimeter (L) of a particle (powder particle) photographed using an electron microscope are obtained, and the circularity is calculated by applying them to the following formula (1). The average circularity is then calculated as the average value of the circularities of 100 randomly selected particles. Circularity = 4πS / L 2 (1)

[0032] The average circularity is not particularly limited, but is preferably, for example, 0.6 or more, 0.65 or more, 0.7 or more, 0.75 or more, 0.8 or more, 0.85 or more, or 0.9 or more. By having an average circularity of a required amount or more, the rolling resistance of the particles when mixed with the base material is reduced, the viscosity of the base material is reduced, and the fluidity of the base material can be improved. In particular, when the average circularity is 0.90 or more, the fluidity of the base material is further increased, so that the powder can be highly filled in the base material, and the thermal expansion coefficient can be easily reduced. On the other hand, the average circularity may be 1 or less.

[0033] The average particle size is not particularly limited, but is preferably 0.1 μm or more, 0.2 μm or more, 0.5 μm or more, 1 μm or more, or 2 μm or more. On the other hand, the average particle size is preferably 100 μm or less, 90 μm or less, 80 μm or less, 70 μm or less, 60 μm or less, or 50 μm or less. The average particle size of the powder can be determined by measuring the particle size distribution using a laser diffraction particle size distribution measuring device, multiplying the calculated particle size value by the relative particle amount (differential volume %), and dividing the result by the total relative particle amount (100 volume %).

[0034] The thermal expansion coefficient of the powder in the 112 plane direction is not particularly limited, but is preferably 0 ppm / °C or less, -0.1 ppm / °C or less, -0.2 ppm / °C or less, -0.3 ppm / °C or less, -0.4 ppm / °C or less, -0.5 ppm / °C or less, -0.6 ppm / °C or less, -0.7 ppm / °C or less, -0.8 ppm / °C or less, -0.9 ppm / °C or less, -1 ppm / °C or less, -1.1 ppm / °C or less, -1.2 ppm / °C or less, -1.3 ppm / °C or less, -1.4 ppm / °C or less, or -1.5 ppm / °C or less. The more negative the thermal expansion coefficient of the powder, the lower the amount of powder added. Therefore, it is better to have a thermal expansion coefficient that is more negative. Therefore, the lower limit of the thermal expansion coefficient of the powder in the 112 plane direction is not particularly limited. The thermal expansion coefficient in the plane direction is measured by the following method. The thermal expansion coefficient of the main phase is analyzed using high-temperature X-ray diffraction (high-temperature XRD). Here, an angle standard sample (Si) is added to the sample and measured using a focused optical system. Specifically, about 10 mass% of an angle standard sample (Si, NIST SRM 640c) is added to each sample and mixed in a mortar. Then, the sample is placed on a sample plate, and the sample is spread with a glass plate so that the sample surface and the sample plate surface are aligned, and measurement (using a focused optical system) is performed at six temperature levels (25 to 300 ° C.). The lattice spacing at each temperature is calculated from the diffraction lines derived from the 112 plane and the 203 plane obtained, and the thermal expansion coefficient of the main phase is analyzed. Note that more detailed measurement conditions will be explained in the examples.

[0035] The thermal expansion coefficient of the powder in the 203 plane direction is not particularly limited, but is preferably 0 ppm / ° C. or less, -0.1 ppm / ° C. or less, -0.2 ppm / ° C. or less, -0.3 ppm / ° C. or less, -0.4 ppm / ° C. or less, -0.5 ppm / ° C. or less, -0.6 ppm / ° C. or less, -0.7 ppm / ° C. or less, -0.8 ppm / ° C. or less, -0.9 ppm / ° C. or less, -1 ppm / ° C. or less, -1.1 ppm / ° C. or less, -1.2 ppm / ° C. or less, -1.3 ppm / ° C. or less, -1.4 ppm / ° C. or less, or -1.5 ppm / ° C. or less. Therefore, the lower limit of the thermal expansion coefficient of the powder in the 203 plane direction is not particularly limited.

[0036] <Powder manufacturing method> The method for producing powder according to the present embodiment will be described below. The method for producing powder according to one embodiment includes a step of producing raw powder (raw powder producing step), a step of forming the raw powder into a spherical shape (spheroidizing step), and a step of crystallizing the raw powder (crystallization step). The method for producing powder according to the present embodiment preferably includes the raw powder producing step, the spheroidizing step, and the crystallization step in this order.

[0037] [Raw material powder preparation process] In the raw material powder preparation process, raw materials are mixed to prepare raw material powder. The raw materials are not particularly limited, but may be zinc oxide or the like as a Zn source, aluminum oxide or aluminum hydroxide or the like as an Al source, and silicon oxide (α-quartz, cristobalite, amorphous silica, etc.) as a Si source.

[0038] The blending amounts of the raw materials are not particularly limited, but may be, for example, Zn source: 17 to 43 mol %, Al source: 9 to 20 mol %, and Si source: 48 to 63 mol %, based on the total amount of the Zn source, Al source, and Si source used.

[0039] In the raw material powder preparation step, in addition to the above-mentioned raw materials, a nucleating agent such as zirconium oxide or titanium oxide may be added to the range that does not affect the thermal expansion coefficient.

[0040] In the raw material mixture, the content of ionic impurities is not particularly limited, but is preferably 500 ppm by mass or less, 450 ppm by mass or less, 400 ppm by mass or less, 350 ppm by mass or less, 300 ppm by mass or less, 250 ppm by mass or less, 200 ppm by mass or less, 150 ppm by mass or less, 100 ppm by mass or less, 0 ppm by mass or less, 80 ppm by mass or less, 70 ppm by mass or less, 60 ppm by mass or less, 50 ppm by mass or less, 40 ppm by mass or less, 30 ppm by mass or less, 20 ppm by mass or less, or 10 ppm by mass or less.

[0041] The method for mixing the raw material oxides is not particularly limited as long as it is a method that is unlikely to mix with alkali metals such as Na, Li, or K, or other metal elements such as Fe. For example, a method of mixing using an agate mortar, a grinder such as a ball mill or a vibration mill, or various mixers can be used.

[0042] In the raw powder preparation process, the raw powder is then placed in a container such as a platinum crucible or an alumina crucible, melted in a heating furnace such as an electric furnace, a high-frequency furnace, or an image furnace, or a flame burner, and then the melt is taken out into air or water and quenched. In this way, raw glass can be obtained. The obtained raw glass is then crushed to obtain raw powder. The method for crushing the raw glass is not particularly limited, and may be, for example, a method using an agate mortar, a ball mill, a vibration mill, a jet mill, a wet jet mill, or the like. The crushing can be performed by either a dry method or a wet method. When crushing by a wet crushing method, for example, the raw powder is mixed with a liquid such as water or alcohol and the raw powder is crushed in a wet method.

[0043] [Spheroidization process] In the spheroidization step, the raw material powder is spheroidized by a powder melting method, in which the raw material powder is introduced into a chemical flame, a thermal plasma, a vertical tubular furnace, or a tower kiln, melted, and spheroidized by its own surface tension.

[0044] In the powder melting method, the particle size distribution after spheroidization can be adjusted by adjusting the particles obtained by pulverizing the raw glass or the particles obtained by granulating the raw powder with a spray dryer or the like to a desired particle size distribution. These particles are charged into a chemical flame or thermal plasma, a vertical tubular furnace or a tower kiln, or the like while suppressing the aggregation of the particles, and melted to perform spheroidization. Alternatively, the spheroidization may be performed by preparing a dispersion liquid of the raw powder dispersed in a solvent or the like, spraying the liquid raw material using a nozzle or the like into a chemical flame or thermal plasma, a vertical tubular furnace or a tower kiln, etc., evaporating the dispersion medium, and then melting the raw powder.

[0045] Here, in the powder melting method, the term "chemical flame" refers to a flame generated by burning a combustible gas with a burner. The combustible gas may be any gas that has a temperature equal to or higher than the melting point of the raw powder, and may be, for example, natural gas, propane gas, acetylene gas, liquefied petroleum gas (LPG), hydrogen, or the like. Such a combustible gas may be used together with air, oxygen, or the like as a combustion-supporting gas. The size, temperature, and other conditions of the chemical flame can be adjusted by the size of the burner and the flow rates of the combustible gas and the combustion-supporting gas.

[0046] [Crystallization process] In the crystallization step, the raw material powder is heated at a high temperature to crystallize it. Any heating device may be used for the crystallization as long as the desired heating temperature can be obtained, and examples of the heating device that can be used include an electric furnace, a rotary kiln, a pusher furnace, and a roller hearth kiln.

[0047] The temperature for heat crystallization (crystallization temperature) is not particularly limited, but is preferably, for example, 750 to 900°C. By setting the heating temperature to a required temperature or higher, the crystallization time can be shortened, and sufficient crystallization can be achieved, thereby increasing the content of the β-quartz solid solution phase. This makes it possible to further reduce the thermal expansion coefficient of the base material containing the powder. On the other hand, by setting the crystallization temperature to a required temperature or lower, crystal phases other than the β-quartz solid solution phase, such as gahnite phase, cristobalite phase, willemite phase, etc., are less likely to be generated, and the thermal expansion coefficient of the base material containing the powder can be further reduced. Note that even with the same composition, the S 001 / S 101 For example, even if the heating temperature differs by 10°C, S 001 / S 101 There can be large differences in

[0048] The heating time (crystallization time) is not particularly limited, but is preferably, for example, 1 to 24 hours. By setting the heating time to the required time or longer, crystallization into the β-quartz solid solution phase is sufficiently performed, and the thermal expansion coefficient of the base material containing the powder can be further reduced. By setting the heating time to the required time or shorter, the cost required for manufacturing the powder can be reduced. By passing through such a crystallization process, the powder according to this embodiment can be obtained.

[0049] The powder obtained in the crystallization step may be an aggregate of a plurality of particles. The aggregate itself may be used as a powder, or the aggregate may be crushed to obtain a powder as necessary. The method for crushing the aggregate is not particularly limited, but for example, a method using an agate mortar, a ball mill, a vibration mill, a jet mill, a wet jet mill, or the like may be used. The crushing may be performed in a dry manner, or may be performed in a wet manner by mixing with a liquid such as water or alcohol. In the wet crushing, the powder of this embodiment is obtained by drying after crushing. The drying method is not particularly limited, but for example, heat drying, vacuum drying, freeze drying, supercritical carbon dioxide drying, or the like may be used.

[0050] In another embodiment, the method for producing the powder may further include a step of classifying the powder so as to obtain a desired average particle size, and a step of surface treatment using a coupling agent. By carrying out the surface treatment, the amount of the powder mixed (loading amount) in the base material can be further increased. As the coupling agent used for the surface treatment, a silane coupling agent, a titanate coupling agent, an aluminate coupling agent, etc. may be used.

[0051] The powder according to this embodiment can be used by mixing with a powder having a different composition (for example, silica, alumina, etc.).

[0052] The powder according to this embodiment can be used as it is or mixed with the powder having a different composition as described above and incorporated into a glass or resin substrate.

[0053] Glass substrates include PbO-B2O3-ZnO, PbO-B2O3-Bi2O3, PbO-V2O5-TeO2, SiO2-ZnO-M 1 2O series (M 1 2O is an alkali metal oxide), SiO2-B2O3-M 1 Glass having a composition such as SiO2-B2O3-M2O (M2O is an alkaline earth metal oxide) can be used.

[0054] The resin substrate is not particularly limited, but examples thereof include epoxy resin, silicone resin, phenol resin, melamine resin, urea resin, unsaturated polyester, fluororesin, polyamide (polyimide, polyamideimide, polyetherimide, etc.), polybutylene terephthalate, polyester (polyethylene terephthalate, etc.), polyphenylene sulfide, wholly aromatic polyester, polysulfone, liquid crystal polymer, polyethersulfone, polycarbonate, maleimide-modified resin, ABS (acrylonitrile-butadiene-styrene) resin, AAS (acrylonitrile-acrylic rubber-styrene) resin, AES (acrylonitrile-ethylene propylene diene rubber-styrene) resin, and mixtures of these resins.

[0055] The amount of powder (filling amount) in the base material is not particularly limited and may be adjusted according to the thermal expansion coefficient after the powder is added, but for example, it is preferably 30 to 95 volume % and more preferably 40 to 90 volume % of the total amount of the base material after the powder is added.

[0056] The powder according to this embodiment has a negatively large thermal expansion coefficient, and therefore can reduce the thermal expansion coefficient of a base material or the like containing the powder. EXAMPLES

[0057] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0058] [Examples 1 to 5, Comparative Example 1] (Raw powder production process) Zinc oxide, aluminum oxide, and silicon dioxide were used as raw materials and mixed in a vibration mixer (Lab RAM II, low-frequency resonant acoustic mixer, manufactured by Resodyn) so as to obtain the molar ratio shown in Table 1. 30 g of this mixture was placed in a platinum crucible and heated in an electric furnace to melt it. At this time, the temperature inside the electric furnace during melting was 1600°C, and the holding time at 1600°C was 30 minutes. After melting, the crucible was submerged in water and rapidly cooled to obtain a raw material glass. The raw material glass was recovered from the platinum crucible, pulverized by a stamp mill, and passed through a nylon sieve with an opening of 77 μm (200 mesh) to obtain raw material powder.

[0059] (crystallization process) The raw material powder was then pulverized and placed in an alumina crucible, and crystallized in an air atmosphere using an electric furnace with the temperature inside the electric furnace set to 800° C. and the holding time at 800° C. for 24 hours. In this way, powder samples according to Examples 1 to 5 and Comparative Example 1 were obtained.

[0060] The properties of the obtained powder samples were evaluated by the methods described below.

[0061] [Identification of crystalline phases] The crystal phase contained in the obtained powder sample was identified by powder X-ray diffraction. Specifically, a horizontal sample type multipurpose X-ray diffractometer (Rigaku Corporation, Ultima IV) was used, and measurements were performed under the following conditions: X-ray source CuKα, tube voltage 40 kV, tube current 40 mA, scan speed 10° / min, 2θ scan range 10°-80°, detector high-speed one-dimensional X-ray detector D / teX Ultra2, optical system focusing method. Figure 3 shows the X-ray diffraction patterns of the powder samples of Examples 1-5 and Comparative Example 1. In all samples, diffraction peaks derived from β-quartz solid solutions composed of ZnO, Al2O3, and SiO2 were confirmed.

[0062] [X-ray diffraction peak ratio S 001 / S 101] The area of ​​each peak was determined by drawing a parabolic background line in the range of 10°≦2θ≦30° using the analysis software Jade 9, and then refining the peaks including the background line and separating them. Note that the diffraction lines from Kα1 and Kα2 overlap in the peaks appearing in the range of 15°≦2θ≦17° and in the range of 24°≦2θ≦27°, respectively, and this was taken into consideration when separating the peaks. In addition, a pseudo-Voigt function was used as a function of the diffraction peaks in the analysis.

[0063] [Thermal expansion coefficient of powder] Using high-temperature X-ray diffraction (XRD), the thermal expansion coefficient of the main phase of β-quartz solid solution was analyzed. Here, an angle standard (Si) was added to the sample and measured using a focused optical system. Specifically, about 10 mass% of an angle standard (Si, NIST SRM 640c) was added to each sample and mixed in a mortar. Then, the sample was placed on a sample plate and spread with a glass plate so that the sample surface was aligned with the sample plate surface, and measurements (using a focused optical system) were performed at temperatures from 100°C to 300°C. The lattice spacing at each temperature was calculated from the obtained diffraction lines (112 plane, 203 plane), and the thermal expansion coefficient of the main phase was analyzed.

[0064] X-ray diffraction measurements were performed using a horizontal-sample multipurpose X-ray diffraction instrument (Rigaku Corporation, UltimaIV). The X-ray source was CuKα, the tube voltage was 40 kV, the tube current was 40 mA, the scan speed was 10° / min, the 2θ scan range was 10°–140°, the detector was a high-speed one-dimensional X-ray detector D / teX Ultra2, the optical system was the focusing method, the measurement stage was a high-temperature sample device, and the measurement atmosphere was N2 flow (30 mL min -1 ), set temperature 100, 150, 200, 250, 300℃, heating rate 10℃min -1 The measurements were taken at intervals of 5 min.

[0065] The analysis was performed as follows. The measurement results at each temperature T were analyzed using the analysis software Jade 9 to obtain the lattice spacing d 220_T , d 400_T and the lattice spacing d of the main phase112_T , d 203_T was calculated. Analysis Software Jade 9 Method Peak fitting Analysis temperature 100, 150, 200, 250, 300℃ Angle range 2θ=46~50°, 65~69.5° Component 2 components (Si 220 planes, main phase 112 planes) (2θ=46~50°) 2 components (Si 400 planes, main phase 203 planes) (2θ=65~69.5°) Background liniar background(2θ=46~50°) parabolic background(2θ=65~69.5°) Peak shape pseudo-Voigt function

[0066] The lattice spacing calculated above is thought to include errors due to sample decentering, since it was measured by heating using a centralized optical system. Therefore, the sample decentering amount (ΔZ) was estimated using the thermal expansion coefficient of Si (known) and the lattice spacing (measured value), and the lattice spacing of the main phase (ZnO-Al2O3-SiO2) was corrected using the following procedure. The lattice spacing at 100°C was used as the reference, and the calculated lattice spacing d at 150°C or higher was calculated as 220_T計算値 was calculated from the literature value of the thermal expansion coefficient of the Si 220 surface (3.5 ppm / ℃, see Int. J. Thermophys, 25, 1, 221-236 (2004)). Next, d 220_T計算値 Substituting into the Bragg equation, the diffraction angle 2θ 220_T計算値 Then, 2θ 220_T実測値 and 2θ 220_T計算値 Difference, Δ2θ 220_T Then, Δ2θ was calculated. 220_T The sample eccentricity ΔZ was calculated by substituting the above into the following equation for eccentricity error (Equation (1)). Note that the goniometer radius R was set to 285 mm.

number

[0067] Next, the diffraction angle 2θ from the 112 plane of the main phase112_T実測値 and the sample eccentricity ΔZ is substituted into the eccentricity error, Δ2θ 112_T was calculated (Equation (2)).

number

[0068] Then, 2θ 112_T実測値 The above-mentioned Δ2θ 112_T Corrected by 2θ 112_T補正値 was calculated. 112_T補正値 Substituting this into the Bragg equation, the corrected lattice spacing d 112_T補正値 Similarly, the corrected lattice spacing d 203_T補正値 was calculated.

[0069] For the measurement temperature T, the corrected lattice spacing d 112_T補正値 A graph is created by plotting the above, and a linear approximation is performed in the range of 100 to 300°C. The slope of the 112_T The thermal expansion coefficient α of the 112 plane of the main phase was calculated using the following formula (3). 112 was calculated.

number

[0070] Similarly, d 203_T補正値 Using this, the thermal expansion coefficient α of the main phase 203 plane is 203 was calculated.

[0071] Table 2 shows the composition of the raw materials (feed composition), S 001 / S 101 Ratio and thermal expansion coefficient α of (112) and (203) planes 112 , α 203 The composition of the raw materials and the powder were almost unchanged.

[0072] [Table 1]

[0073] It was found that the powder samples of Examples 1 to 5 had thermal expansion coefficients that were negatively larger than that of the powder sample of Comparative Example 1.

[0074] Figure 4 shows the thermal expansion coefficient vs. S 001 / S 101 The ratio of the thermal expansion coefficient in the (203) plane to the S 001 / S 101 The thermal expansion coefficients in each direction and the S ratio are plotted. 001 / S 101 It was found that there is a linear relationship with a negative slope between the ratio.

Claims

1. A powder comprising: ZnO, Al 2 O 3 and SiO 2 The components are ZnO, Al 2 O 3 and SiO 2 In the ternary phase diagram of (ZnO (mol%), Al 2 O 3 (mol%), SiO 2 (mol%)) = (ZnO (mol%), Al 2 O 3 (mol%), SiO 2 (mol%))=(24,13,63), (19,18,63), (32,13,55), and (28,17,55). In the X-ray diffraction pattern, the area S of a peak appearing in the range of 15°≦2θ≦17° is 001 and the area S of the peak appearing in the range of 24°≦2θ≦27° 101 Ratio to (S 001 / S 101 ) is equal to or greater than 0.001 and equal to or less than 0.07 powder.

2. 2. The powder according to claim 1 , The powder contains 50% by mass or more of β-quartz solid solution as a crystalline phase based on the total amount of the powder. powder.

3. The powder according to claim 1 or 2, The total content of Li, Na and K is 500 mass ppm or less based on the total amount of the powder. powder.

4. The powder according to claim 1 or 2, The average circularity is 0.6 or more. powder.

Citation Information

Patent Citations

  • Low thermal expansion ceramics and filling material for sealing semiconductor

    JP1990208256A

  • Powder and mixed powder

    WO2019177112A1